Design and Analysis of In-Wheel Double Stator Slotted Rotor BLDC Motor for Electric Bicycle Application - S. Farina; R.N. Firdaus; F. Azhar; M. Azri; M. S. Ahmad; R. Suhairi; A. Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2018)
This paper discusses about design and analysis of double stator slotted rotor (DSSR) BLDC motor for electric bicycle application. Usually single stator (SS) BLDC motor is used in an electric bicycle. This type of motor has low performance and need to be charged regularly. The objective of this research is to design and analysis DSSR motor that have high torque. At starts, design specification for the electric bicycle is calculated. Next, design process for DSSR is carried out by using the desired parameter. Lastly, analysis for double stator slotted rotor is simulated using FEM. Result for average back emf, average inductance, inner stator flux density, outer stator flux density, average torque and estimate torque constant is obtained. Result for average torque from FEM archieve the requirement of motor torque for DSSR design where the maximum average torque is 16.2 Nm. This research will give benefit to mankind and society in term of environment protection and energy consumption.